Punching Shear Strength Prediction for Reinforced Concrete Flat Slabs without Shear Reinforcement - Hani Qadan; Amjad A. Yasin; Ahmad B. Malkawi; Muhmmad I. M Rjoub (Salehan Institute of Higher Education, 2022)
Failure of flat slabs usually occurs by punching shear mode. Current structural codes provide an experience-based design provision for punching shear strength which is often associated with high bias and variance. This paper investigates the effect of adding a horizontal reinforcement mesh at the top of the slab-column connection zone on punching the shear strength of flat slabs. A new equation considering the effect of adding this mesh was proposed to determine the punching shear strength. The proposed equation is based on the Critical Shear Crack Theory combined with the analysis of results extracted from previous experimental and theoretical studies. Moreover, the equation of load-rotation curves for different steel ratios together with the failure criterion curves were evaluated to get the design points. The investigated parameters were the slab thicknesses and dimensions, concrete strengths, size of the supporting column, and steel ratios. The model was validated using a new set of specimens and the results were also compared with the predictions of different international design codes (ACI318, BS8110, AS3600, and Eurocode 2). Statistical analysis provides that the proposed equation can predict the punching shear strength with a level of high accuracy (Mean Square Error =2.5%, Standard Deviation =0.104, Mean=1.0) and over a wide range of reinforcement ratios and compressive strengths of concrete. Most of the predictions were conservative with an underestimation rate of 12%. Doi: 10.28991/CEJ-2022-08-01-013 Full Text: PDF